Ablation of sphingosine kinase 2 suppresses fatty liver-associated hepatocellular carcinoma via downregulation of ceramide transfer protein - Xin Tracy Liu; Long Hoa Chung; Da Liu; Jinbiao Chen; Yu Huang; Jonathan D. Teo; Xingxing Daisy Han; Yinan Zhao; Fiona H. X. Guan; Collin Tran; Jun Yup Lee; Timothy A. Couttas; et al. (Oncogenesis, 2022)
Abstract Hepatocellular carcinoma (HCC) accounts for 90% of primary liver cancer, the third leading cause of cancer-associated death worldwide. With the increasing prevalence of metabolic conditions, non-alcoholic fatty liver disease (NAFLD) is emerging as the fastest-growing HCC risk factor, and it imposes an additional layer of difficulty in HCC management. Dysregulated hepatic lipids are generally believed to constitute a deleterious environment cultivating the development of NAFLD-associated HCC. However, exactly which lipids or lipid regulators drive this process remains elusive. We report herein that sphingosine kinase 2 (SphK2), a key sphingolipid metabolic enzyme, plays a critical role in NAFLD-associated HCC. Ablation of Sphk2 suppressed HCC development in NAFLD livers via inhibition of hepatocyte proliferation both in vivo and in vitro. Mechanistically, SphK2 deficiency led to downregulation of ceramide transfer protein (CERT) that, in turn, decreased the ratio of pro-cancer sphingomyelin (SM) to anti-cancer ceramide. Overexpression of CERT restored hepatocyte proliferation, colony growth and cell cycle progression. In conclusion, the current study demonstrates that SphK2 is an essential lipid regulator in NAFLD-associated HCC, providing experimental evidence to support clinical trials of SphK2 inhibitors as systemic therapies against HCC.